Suicides in Czech Republic, Slovakia, Hungary, and Poland in 1990-2019: Epidemiological Patterns and Trends in European and Global Context - Lochmannová, Alena; Majdan, Marek; Šafr, Miroslav (Archives of medical research, 2025)
BACKGROUND: Suicides are a major public health problem with serious consequences for societies. AIM: To compare epidemiological patterns and trends of suicides in the Czech Republic, Slovakia, Hungary, and Poland in 1990-2019, and analyze them in the European and global context. METHODS: A trend analysis was conducted in Czech Republic, Slovakia, Hungary, Poland, in Western Europe and on global level for 1990-2019. All data were obtained from the Global Burden of Diseases study 2019. Numbers and age-standardized rates of deaths and Years of Life Lost (YLL) due to suicides were analyzed, stratified by sex and age (0-14 years old, 15-49 years old, 50-69 years old, 70+ years). RESULTS: In 2019, 759,028 suicides occurred globally, 17,408 (2.3%) in Central Europe. The proportion of males was substantially larger, compared to the global and Western European levels (e.g., 82 vs. 69 and 75%, respectively). The highest rates of suicide were in Hungary (19.7 per 100,000), lowest in Slovakia (12.8); the rate in Central Europe was higher than the global rate (15.2 vs. 9.8), and the rate in Western Europe (11.4). A steady decline of rates was observed in all countries, particularly in Hungary. In Czech Republic we found an increasing relative importance of suicides among people 70 years and older. CONCLUSIONS: Death rates due to suicides have been declining in the analyzed countries, but some characteristics and trends when compared to global and regional estimates, such as substantially higher proportion of male suicides or high death rates among the elderly warrant specifically tailored preventative action coordinated by governments with community involvement.
Keywords: Young Adult; Male; Child, Preschool; Slovakia; Prevention; Slovenská republika; mladý dospělý; Adolescent; Infant; Česká republika; Child; Poland; Europe; dítě; Adult; Aged; dospělí; sebevražda; mužské pohlaví; senioři; Epidemiology; mladiství; Central Europe; Czech Republic; Evropa; Maďarsko; předškolní dítě; lidé; Suicide; ženské pohlaví; Humans; kojenec; Hungary; Death; Female; Polsko; lidé středního věku; Middle Aged